Dampak Perubahan Iklim Terdahap Dinamika Air Didalam Tanah Dan Implikasinya Pada Pertanian - Gulo, Zefri William; hia, sastra alberta (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Climate change has caused significant increases in temperature and changes in rainfall patterns, which have an impact on soil water dynamics and agricultural productivity. This research analyzes the relationship between climate change and soil moisture through climate data collection and simulations using the Soil and Water Assessment Tool (SWAT). The research results show that increasing temperature and uneven distribution of rainfall cause a decrease in soil moisture, especially on sandy land and land with steep topography. The implications of this decrease in soil moisture include increased irrigation requirements, reduced crop productivity, and increased risk of erosion. Adaptation strategies such as implementing precision irrigation, using mulch, and managing planting patterns are important to maintain soil moisture and agricultural productivity. By implementing this adaptive approach, it is hoped that the agricultural sector will be able to increase resilience to the impacts of climate change.